Individual and system influences on waiting time for substance abuse treatment - Carr, Carey J.A. (2007)
Waiting time is a contemporary reality of many drug abuse treatment programs, resulting in substantial problems for substance users and society. Individual and system factors that influence waiting time are diverse and may vary at different points in the treatment continuum. This study assessed waiting time preceding clinical assessment at a centralized intake unit and during the period after the assessment but before treatment entry. The present study included 577 substance abusers who were enrolled in a large clinical trial of two brief treatment interventions in a midsize metropolitan area in Ohio. Bivariate analyses identified individual and system factors that influenced preassessment and postassessment waiting time, as well as total wait to treatment services. Multivariate analyses demonstrated that longer wait time for an assessment is influenced by being court referred, less belief in having a substance abuse problem, and less desire for change. A shorter wait to actually enter treatment is predicted by having a case manager, being more ready for treatment, and having less severe employment and alcohol problems. The different influences present during the two waiting periods suggest that assessment and treatment programs need to implement system changes and entry enhancement interventions that are specific to the needs of substance abusers at each waiting period.